Semiotic Study of Symbols in Dan Brownâ€™s â€œInfernoâ€ Novel - Kusumoriny, Laksmy Ady; Amalia, Shinta Tisya (Jurnal Ilmiah Humanika, 2019)
This study is aimed to describe semiotic studies concerning symbols and their meanings found in Dan Brown’s Inferno (2013) novel. This study uses a descriptive qualitative method which tries to identify, to analyze, and to describe the symbols found in Dan Brown’s Inferno novel using semiotic theory by Charles Sanders Peirce (1991). The data for the finding and analysis were taken from Dan Brown’s Inferno novel. The result of this study shows 30 symbols which are related to Christianity, Dante Alighieri’s life, The Seven Deadly Sins, The Divine Comedy, The Black Death, Transhumanism and Humanism movement.